Temporality and Patterns of Metastatic Recurrence in Node-Positive Breast Cancer Following Trimodality Therapy: Opportunity for Improved Oligometastases Detection and Salvage Local Therapy. (February 2022) - Ariani, Rojine; Hwang, Lindsay; Maliglig, Ana M.; Ragab, Omar; Ye, Jason C.
Abstract : Objectives: There is evidence that detection and treatment of oligometastases (⩽5 lesions) may improve survival in breast cancer patients. However, there are no current national guidelines for screening of early, asymptomatic metastases. This study examined the patterns and timing of recurrence with respect to survival in node-positive breast cancer (NPBC) patients at higher risk for developing metastases. Methods: A single-institution retrospective review of NPBC patients treated with trimodality therapy was performed to collect patient and disease characteristics, recurrence location, method of detection, and survival outcome. Univariate and multivariate analyses were done to identify factors associated with recurrence. Results: Ninety-four NPBC patients treated at a safety-net hospital between 2008 and 2019 were identified. Twenty-one developed recurrence and were divided into oligometastatic (OM) (n=10) or diffusely metastatic (DM) (n=11) subgroups. Median recurrence-free survival in OM and DM was 18 and 36 months, respectively. Median overall survival (OS) for OM was not reached. Median OS for DM was 57 months. Four patients with OM progressed to diffuse disease in a median period of 17 months; median survival thereafter was 57 months. All patients with recurrence had distant metastases on initial detection, with the most common site being bone (14). Recurrence was most frequently detected by computed tomography (CT) (13), with the majority of disease located within the thorax region. Conclusions: All NPBC patients had distant metastasis at time of recurrence. Patients with OM had shorter interval to recurrence yet longer OS compared with DM. This study highlights improved surveillance imaging for timely detection of OM breast cancer that may yet be amenable to aggressive local salvage therapy to prevent progression to diffuse disease. Abstract : Supplemental Digital Content is available in the text.